Descontinuidade do seguimento ambulatorial de crianças egressas de Unidades de Terapia Intensiva Neonatal: a perspectiva das mães - Ieda Aparecida Diniz (2016)
This paper aims at analyzing the discontinuity of the outpatient follow-up with children coming from neonatal intensive care units under the perspective of their mothers. It is an exploratory study with a qualitative approach, oriented by dialectics. Participants are 15 mothers of 19 children aged up to 2 years, egress from neonatal intensive care units in discontinuity of the outpatient follow-up. The scenario was the childrens homes. The field research started in two outpatient clinics for follow-up of at-risk children in Belo Horizonte, Minas Gerais, when the children in discontinuity were identified. The data was obtained by means of semi-structured interviews and the field work notes. The data analysis was accomplished though the thematic Content Analysis, constructing four empirical classes: the mothers understanding on the need of care to their children; the outpatient follow-up and the benefits to the health of at-risk children; socioeconomic factors and daily life aspects that interfere in the maintenance of the outpatient follow-up; and aspects related to the outpatient follow-up service and their contribution for the discontinuity of the outpatient follow-up. The analysis revealed the understanding of mothers on the need of care from what is observed on the child and what they learn within their care experience, what added to the non-awareness about the risks and the possibility of impacts on the childs development. The mothers present a superficial understanding about the follow-up and its benefits to their childs needs. Socioeconomic factors and daily life aspects, which predispose the follow-up discontinuity, are: distance to the outpatient clinics; public transport deficiency; financial difficulties; lack of social and familiar environment; the mothers employment; loss of a relative; postpartum depression and the hospitalization of the child. Some aspects related to the service were also found such as the unavailability of service hours, double booking for appointments at the same time, service long delays, inefficient communication between mothers and health professionals and inefficiency on the search for absent children. It turns evident the necessity to consider aspects experienced by each family to assure access to the follow-up services. Furthermore, the results indicate the need for developing other studies in order to combine more elements for the comprehension of this phenomenon in the Brazilian reality, contemplating the discontinuity from the hospital release, the relation with maternal health conditions. As well as other studies with different methodologies, which will enable greater knowledge on the factors related to carers physical and emotional health, socioeconomic and environmental aspects, which were considered part f the discontinuity.